PEMBERDAYAAN MASYARAKAT MELALUI PENERAPAN TEKNOLOGI KARBONASI SAMPAH ORGANIK UNTUK MENGATASI PERMASALAHAN LINGKUNGAN DAN ENERGI DI BOYOLALI - Danar Susilo Wijayanto; Deni Andriyansyah; Siti Nurrohmah; Latifah Nurul Q.; Wijayasari D.W. Wijayasari D.W.; Krisnawan Suko Raharjo; Abdul Aziz Nur R.; Erni Latifah W; Susy Ermawaty; Athia Tamyizatun N; Amin Marlinda C. (Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2013)
KKN-PPM program objectives are : (1) Increase awareness and empathy students to weak economy community problems, resulting in a change in behaviour of students, intuitions and the target group, in this case is the Dibal village community by KKN-PPM programs, (2) Solve environmental problems caused by waste in the Dibal village and create a clean and comfortable environment with environmentally concious socialization and support go green movement, (3) Implementing technology carbonated organic waste into bio-briquettes as an alternative fuel in Dibal village.KKN-PPM activities carried out with of continuous activities series, namely : (1) disseminasion to Dibal community, (2) Procurement of bio-briquette maker equipment : carboning drum, pail, smoothing tool/sieve/strainer, mixer, bio-briquette mold machine, and stove, (3) Training how to make bio-briquette, (4) training how to use bio-briquette.The program implementation results are : (1) Dibal community continuosly able to utilize waste into environmental issues as an alternative fuel through pyrolysis combustion technologies such as bio-briquette, (2) Establishment of the independence of the target communities in managing organic waste into alternative fuel bio-briquette, (3) Dibal villagers applying bio-briquette as an alternative fuel.